2023
DOI: 10.1097/hjh.0000000000003521
|View full text |Cite
|
Sign up to set email alerts
|

Salt intake, blood pressure and cardiovascular disease mortality in England, 2003–2018

Jing Song,
Monique Tan,
Changqiong Wang
et al.

Abstract: Objectives: The aim of this study was to assess the changes in salt intake and concomitant changes in blood pressure (BP) and cardiovascular disease (CVD) mortality in England from 2003 to 2018. Methods: National surveys and death registration data were used for the analysis of salt intake as measured by 24-h urinary sodium excretion (449–1069 participants per year), BP (2651–6738 participants per year) and CVD mortality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…An intervention in China, where food consumed at home is the primary source of sodium intake, may have been successful because it is easier to reach individuals rather than large industries [ 44 ]. The United Kingdom, where the main sources of sodium more closely match that of the United States, demonstrated that comprehensive sodium reduction interventions targeted at industry can reduce the intake of sodium, but the improvements can also be reversed if the programs and policies are not sustained [ 45 ]. In 2021, the FDA took steps toward sodium reduction in the food supply by introducing near-term voluntary sodium reduction guidance [ 46 ], but more action is urgently needed—CVD continues to be a leading cause of death and contributes to significant racial and ethnic disparities.…”
Section: Discussionmentioning
confidence: 99%
“…An intervention in China, where food consumed at home is the primary source of sodium intake, may have been successful because it is easier to reach individuals rather than large industries [ 44 ]. The United Kingdom, where the main sources of sodium more closely match that of the United States, demonstrated that comprehensive sodium reduction interventions targeted at industry can reduce the intake of sodium, but the improvements can also be reversed if the programs and policies are not sustained [ 45 ]. In 2021, the FDA took steps toward sodium reduction in the food supply by introducing near-term voluntary sodium reduction guidance [ 46 ], but more action is urgently needed—CVD continues to be a leading cause of death and contributes to significant racial and ethnic disparities.…”
Section: Discussionmentioning
confidence: 99%
“…The report comes as research published in the Journal of Hypertension found that progress made by the UK’s salt reduction programme had stalled since 2014 after responsibility was handed over to the food industry 2…”
Section: Salt Reductionmentioning
confidence: 99%